The Effect of Service Quality on Customer Loyalty Through Perceived Value and Customer Satisfaction of Jakarta Mobile Banking Application - Teguh Sriwidadi; Hartiwi Prabowo (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: This study aims to examine the form of service quality which has profound effects on the way customers interact with firms to create positive service outcomes i.e., service quality, perceived value, customer satisfaction, and customer loyalty. Therefore, the main objective of this study is to examine the service quality’s impact on the user's perceived value, satisfaction, and loyalty in mobile banking.Methodology: This study uses a quantitative research method. The data has been collected from 498 service users through the online survey. Finding: Structural Equation Modelling is applied by using the PLS-SEM program to test the model. The study concluded that mobile banking service quality positively and significantly affects customer perceived value, customer satisfaction, and customer loyalty. Customer perceived value positively and significantly affects customer satisfaction, significantly but negatively affects customer loyalty, and customer satisfaction positively and significantly affects customer loyalty. Conclusion: This research has differences and similarities with the results of previous studies. This difference is caused by several things such as regional characteristics and participating respondents. The characteristics and behavior of consumers are unique so there may be differences in the results of the research conducted. The research results obtained from the hypothesis prove that the greater the influence of service quality, the greater the perceived value of the mobile banking application, and better customer service quality decreases customer loyalty, better customer service will further increase customer satisfaction. Better perceived value will further increase customer satisfaction, and better customer satisfaction increases customer loyalty.